Penicillin Allergy Skin Testing in the Inpatient Setting - Justo, Julie Ann (Pharmacy (Basel), 2019)
The consequences of a documented penicillin allergy in the medical record are especially troublesome in acutely ill, hospitalized patients. A penicillin allergy label may lead to alternative or second line therapies resulting in adverse drug events, negative clinical outcomes and increased costs. Reconciling penicillin allergies is a necessity to facilitate early, optimal therapy and is a shared responsibility among the healthcare team. Penicillin skin testing (PST) has been utilized successfully in hospitalized patients to de-label erroneous penicillin allergies and optimize antibiotic therapy. This targeted review aims to discuss the practical development and implementation of PST in the inpatient setting. This includes a needs assessment checklist with common considerations allowing for customization to one’s institution based on available personnel, time, and technological resources.